Patients' Shift from Public to Private Primary Health Care Providers in Lithuania: Analysis of the Main Reasons - Paulius Žvinakis MPH; Roberta Kalibataitė DMD; Vytenis Kalibatas MD, MPH, PhD (SAGE Publishing, 2021)
Aims Lithuania is one of the countries where public and private primary health care (PHC) providers compete for patients. Patients continuously shift from public to PHC providers, but an analysis of the main reasons was never performed. This study aimed to analyze the reasons why patients shift from public to private PHC providers and identify the associations between the reasons and demographic characteristics of the patients. Methods A cross-sectional study based on a phone questionnaire was conducted among patients who shifted from public to private primary health care (PHC) providers. A total of 810 phone calls were made, and 572 telephone surveys were completed. The response rate was 70.49%. The difference between the proportions was assessed using the Z-test. The association between categorical variables was assessed using the chi-square test. Results The study identified the following main reasons: long queues to obtain family physician appointments (23.6%), inconvenient location of public's institution department (20.1%), patients relocating (19.2%), enrolment at a former family physician who transitioned from a public to private PHC institution (10.5%), and long waiting time at the family physician's office for the appointment (9.4%). Some statistically significant correlations were found between the specific reasons for shifting from public to private PHC organizations and patients' demographic characteristics. Conclusions Personal reasons are the most common reasons for shifting from public to private PHC providers (43.36% of the respondents), following the reasons related exclusively to the family physician (25.17%) and related PHC institutions only (24.9%).